The Effectiveness of Duolingo and Busuu Apps to Improve English Vocabulary Mastery The Case of Second Grade Students of Ma Yarobi Grobogan - Rizki Alviana; Suwandi; Ajeng Setyorini (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
Vocabulary is crucial in teaching English and mastering the four basic skills. This study aimed to evaluate the vocabulary mastery of second-grade students at MA YAROBI Grobogan before and after using Duolingo and Busuu applications, and to measure significant differences in their vocabulary understanding. The quasi-experimental design involved 61 students. Data were collected through pre-tests, post-tests, and questionnaires. Results indicated a significant increase in vocabulary mastery, with average pre-test scores of 32.80 and 32.48, and post-test scores rising to 82.00 and 80.06. The t-test showed a significant difference (t = -16.900, p < 0.001). Most students responded positively, finding the applications helpful and enjoyable.